Use Pattern of Information Channels by the Scientists and Engineers: A Case Study - Senthilkumaran, P.; Vadivel, V. (Journal of Information and Knowledge, 2014)
This paper reveals the use pattern of information channels by the scientists of CECRI, Karaikudi and engineers of BHEL, Tiruchirappali, Tamil Nadu. The data analyzed from the questionnaires showed that most of the scientists and engineers make use of formal channels more frequently than informal channels. Scientists and engineers collected most of their information through printed media. Most of the scientists have contact with persons elsewhere in their own establishment (informal channel). Most of the scientists and engineers depend heavily on scientific periodicals (formal channel) for getting their information. 'While pursuing to learn a new field' is the occasion through which the engineers receive their information; whereas, most of the scientists receive their information through 'while searching specifically'. Both of them feel that all communication channels that they need should be available in the library. Most of the scientists and engineers agree that easy accessibility makes them to access a particular information source. Scientists do their work in central laboratories; whereas, engineers do their work in divisions. Engineers apply their collected information for development task; whereas, scientists use it for their research purpose. Though the collected information is applied to various tasks - the mode of ac~uisition of information by scientists and engineers is same. Engineers and scientists attended conferences less frequently. The channel, library bulletin, provides most of the information on what is published in their field for both scientists and engineers. Fifty percent of engineers and 33.3% of scientists make 5 to 10 visits to their library in a month. Engineers spend more than 20 minutes to scan various communication channels for a particular information; whereas, scientists spend more than 40 minutes for it.